2022
DOI: 10.1038/s41597-022-01183-y
|View full text |Cite|
|
Sign up to set email alerts
|

China’s environmental policy intensity for 1978–2019

Abstract: Improving the measurement of environmental policy intensity would affect not only the selection of variables in environmental policy research but also the research conclusions when evaluating policy effects. Because direct evaluation is lacking, the existing research usually applies data such as pollutant emission data, or the number of policies to construct proxy variables. However, these proxy variables are affected by many assumptions and different selection criteria, and they are inevitably accompanied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…There are numerous factors affecting the global environment while industrial activities are the main reasons for environmental deterioration. According to Zhang et al [ 2 ], industrial activities of firms are widely believed to be the main cause of environmental problems. In fact, the emissions of SO, NO, and smoke from these activities are responsible for 88.15, 67.60, and 83.65 percent of total emission, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous factors affecting the global environment while industrial activities are the main reasons for environmental deterioration. According to Zhang et al [ 2 ], industrial activities of firms are widely believed to be the main cause of environmental problems. In fact, the emissions of SO, NO, and smoke from these activities are responsible for 88.15, 67.60, and 83.65 percent of total emission, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [ 3 ] support this argument and found that 80% of environmental pollution is due to operations and production activities of firms in China. Despite this, Chinese firms have generally failed to invest in green initiatives due to the negative externalities of pollution [ 2 , 4 ]. Liao et al [ 5 ] warn that prioritizing short-term economic growth over environmental concerns can have severe consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we follow the methods of Li et al 25 about quantifying corporate culture based on latest machine learning techniques and Zhang et al 26 about constructing a dictionary of environmental characteristics to measure corporate sustainability disclosure. Specifically, we first refer to Zhang et al 's approach to identify sustainability related seed words and then follow Li et al 's approach to process text documents and expand seed words to find their synonyms based on word2vec algorithm.…”
Section: Background and Summarymentioning
confidence: 99%
“…Especially over the past 10 years, the negative impact of environmental degradation has been prominent, ranging from ecological destruction and health loss to agricultural productivity decline and global warming. Meanwhile, the Chinese government has gradually realized the importance of environmental governance and has promulgated a series of environmental policies that have improved environmental quality to a certain extent (Zhang et al, 2022). Even so, China's economic system remains fragile, and its environmental carrying capacity is still facing enormous challenges (Ronald et al, 2017).…”
Section: Introductionmentioning
confidence: 99%